Kajian Ayat-Ayat tentang Hak Hidup, Kebebasan Beragama, dan Martabat Manusia dalam Perspektif Imam Al-Qurtubi dalam Kitab Al-Jami’ li Ahkam al-Quran - Jadidah, Nur (Maliki Interdisciplinary Journal, 2026)
This study explores the principles of the right to life, liberty, and human dignity as presented in the Qur'an, specifically through the interpretation of Imam al-Qurṭubī in al-Jāmi‘ li Aḥkām al-Qur’ān. As a renowned classical interpreter, al-Qurṭubī offers a legal interpretation that is enriched with linguistic analysis, social context, and legal arguments. The purpose of this research is to investigate how certain verses related to the right to life, such as QS. al-Mā’idah 5:32, verses concerning religious freedom like QS. al-Baqarah 2:256, and verses addressing human dignity such as QS. al-Isrā’ 17:70 are understood and elaborated from his perspective. By employing a literature review and thematic analysis, this study reveals that al-Qurṭubī emphasizes that the right to life is a fundamental principle safeguarded by the provisions of sharia law; freedom, particularly in religious matters, is respected within the limitations necessary to maintain public order; and human dignity is a universal value bestowed by God upon all humanity without discrimination. Al-Qurṭubī's interpretation illustrates that the teachings of the Qur'an have a robust foundation in the values of human rights, even when framed within traditional Islamic law. This research aims to enhance the understanding of the contributions of classical interpretations to contemporary discussions on human rights.